2019
DOI: 10.1002/ajmg.c.31698
|View full text |Cite
|
Sign up to set email alerts
|

Three additional de novo CTCF mutations in Chinese patients help to define an emerging neurodevelopmental disorder

Abstract: CCCTC‐binding factor (CTCF) is an important regulator for global genomic organization and gene expression. CTCF gene had been implicated in a novel disorder characterized by intellectual disability, feeding difficulty, developmental delay and microcephaly. So far, four patients have been reported with de novo CTCF mutations. We reported three additional Chinese patients with de novo variants in CTCF. The new evidence helped to establish the clinical validity between CTCF and the emerging disorder. We described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…p.(Arg567Trp) has been reported in two individuals previously. 7,9 All missense variants were located in exons encoding one of the 11 zinc fingers. Of note, the majority (6/8) of LGD variants were located in exons 3 and 4, just upstream of or at the start of the zinc finger domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p.(Arg567Trp) has been reported in two individuals previously. 7,9 All missense variants were located in exons encoding one of the 11 zinc fingers. Of note, the majority (6/8) of LGD variants were located in exons 3 and 4, just upstream of or at the start of the zinc finger domains.…”
Section: Resultsmentioning
confidence: 99%
“…A de novo frameshift variant was identified in a girl with developmental delay, short stature, severe microcephaly, heart defects, and various other anomalies, 8 and very recently, two frameshifting and the same missense variant as in Gregor et al 7 were reported in three Chinese individuals with ID, feeding difficulties, and microcephaly. 9 Additionally, two larger deletions of 1.1 and 1.6 Mb, respectively, encompassing CTCF , were identified in individuals with developmental delay and growth impairment. 10 Further studies reported the identification of CTCF variants in large cohorts with various clinical indications but did not provide detailed clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…So far only seven patients have been reported with de novo CTCF mutations (MIM #615502) 27 33–35. Consistent clinical features among these patients included developmental delay/intellectual disability, hypotonia, early feeding difficulty and microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study reported an additional individual of MRD21 with a different de novo CTCF frameshift mutation (Bastaki et al, 2017). Recent studies independently reported 2, 3, and 39 additional individuals of MRD21 with pathogenic variants of CTCF (Hori et al, 2017;Chen et al, 2019;Konrad et al, 2019). Finally, a human genetic study showed strong associations between CTCF SNPs and schizophrenia in multiple cohorts (Juraeva et al, 2014).…”
Section: D Genome Dysregulation Of Clustered Pcdhs By Ctcfmentioning
confidence: 95%
“…De novo mutations of CTCF in humans causes the type 21 of autosomal dominant mental retardation (MRD21) (Gregor et al, 2013;Bastaki et al, 2017;Hori et al, 2017;Chen et al, 2019;Konrad et al, 2019). This rare condition is first described in four individuals with intellectual disability, microcephaly, and growth retardation.…”
Section: D Genome Dysregulation Of Clustered Pcdhs By Ctcfmentioning
confidence: 99%